The GIRAFE phase II trial on MVCT-based "volumes of the day" and "dose of the day" addresses when and how to implement adaptive radiotherapy for locally advanced head and neck cancer. (May 2019) - Esteyrie, Vincent; Gleyzolle, Baptiste; Lusque, Amélie; Graff, Pierre; Modesto, Anouchka; Rives, Michel; Lapeyre, Michel; Desrousseaux, Jacques; Graulières, Eliane; Hangard, Gregory; Arnaud, François-Xavier; Ferrand, Regis; et al.
Highlights: The GIRAFE trial will evaluate an adaptive radiotherapy method. 48 patients will be included. They will undergo 4 intermediate re-planning CTs ( iCTs) and 35 daily MVCT. MVCT adaptive segmentation will be compared with manual recontouring. Deformable contour deformation on iCTs will be compared with manual recontouring. Abstract: During exclusive curative radiotherapy for head and neck tumors, the patient's organs at risk (OAR) and target volumes frequently change size and shape, leading to a risk of higher toxicity and lower control than expected on planned dosimetry. Adaptive radiotherapy is often necessary but 1) tools are needed to define the optimal time for replanning, and 2) the subsequent workflow is time-consuming. We designed a prospective study to evaluate 1) the validity of automatically deformed contours on the daily MVCT, in order to safely use the "dose-of the day" tool to check daily if replanning is necessary; 2) the automatically deformed contours on the replanning CT and the time gained in the replanning workflow. Forty-eight patients with T3-T4 and/or involved node >2 cm head and neck squamous cell carcinomas, planned for curative radiotherapy without surgery, will be enrolled. They will undergo treatment with helical IMRT including daily repositioning MVCTs. The contours proposed will be compared weekly on intermediate planning CTs (iCTs) on weeks 3, 4, 5 and 6. On these iCTs both manual recontouring and automated deformable registration of the initial contours will be compared with the contours automatically defined on the MVCT. The primary objective is to evaluate the Dice similarity coefficient (DSC) of the volumes of each parotid gland. The secondary objectives will evaluate, for target volumes and all OARs: the DSC, the mean distance to agreement, and the average surface-to-surface distance. Time between the automatic and the manual recontouring workflows will be compared.